2016
DOI: 10.1007/s12325-016-0373-y
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Brinzolamide, a Topical Carbonic Anhydrase Inhibitor, on Corneal Endothelial Cells

Abstract: Patients treated with LT + BR showed significant IOP reduction. However, the use of brinzolamide in addition to latanoprost had no influence on CECs during the one-year follow-up period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 14 publications
0
12
0
1
Order By: Relevance
“…15 Similarly, the ECD was reported not to vary significantly during the 48-week follow-up period in cases using latanoprost. 16 Kwon et al 17 that glaucoma patients using BB or prostaglandin analog had corneal ECDs similar to those of nonmedicated individuals. The authors thought that the drug concentration in the aqueous humor did not reach the toxic levels enough to reduce the number of endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…15 Similarly, the ECD was reported not to vary significantly during the 48-week follow-up period in cases using latanoprost. 16 Kwon et al 17 that glaucoma patients using BB or prostaglandin analog had corneal ECDs similar to those of nonmedicated individuals. The authors thought that the drug concentration in the aqueous humor did not reach the toxic levels enough to reduce the number of endothelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…This study was performed with approval of University of Health Sciences, Izmir Tepecik Training and Research Hospital's Medical Research Ethical Committee (approval number: 2019/ [16][17][18][19][20][21][22] and in line with ethical principles of Declaration of Helsinki. Written consent forms were received from all participants.…”
Section: Methodsmentioning
confidence: 99%
“…Several randomized clinical trials reported that the non-fixed combination of latanoprost 0.005% and brinzolamide 1% exerts a better IOP reducing effect than latanoprost monotherapy ( Shoji et al, 2005 ; Nakamoto and Yasuda, 2007 ; Nakano et al, 2016 ). A comparative study demonstrated that LBz-nFC provides a more sustained IOP lowering effect than LT-nFC.…”
Section: Topical Non-fixed Combination Of Two Agentsmentioning
confidence: 99%
“…BLZ is a non-competitive, effective, and very specific carbonic anhydrase inhibitor for the treatment of glaucoma. 3 Clinically, BLZ ocular suspension was mainly used as a first-line antiglaucoma medication following a dosage of one drop each time and twice a day (preferably three times a day). However, its use has been limited by a number of factors, including systemic adverse events (taste aversion), ocular adverse events (eye burning sensation and stinging pain), and relatively high prices.…”
Section: Introductionmentioning
confidence: 99%